2007
DOI: 10.1016/j.cplett.2007.10.065
|View full text |Cite
|
Sign up to set email alerts
|

Reactivity of Au25 clusters with Au3+

Abstract: We report the instantaneous decomposition of the small molecular gold cluster, Au 25 SG 18 (SG-glutathione thiolate) in the presence of externally added chloroaurate ions resulting in the instantaneous formation of the insoluble gold-glutathione polymer. The rate of decomposition, however, was much slower for the metal ions such as Ag + , Fe 3+ , Cu 2+ , Ni 2+ , Cd 2+ , Zn 2+ and Sr 2+ . This chemical reactivity is shown to have no direct correlation with the electrochemical potential of the added ions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2009
2009
2012
2012

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 57 publications
(25 citation statements)
references
References 16 publications
(20 reference statements)
0
25
0
Order By: Relevance
“…Etching of gold nanoparticles by excess thiols is known. [12][13][14][15]20] During interfacial etching at 25 8C, octanethiol etches Au 25 at the water-toluene interface and the etched gold atoms along with some glutathione ligands form Au I SG thiolate, which precipitates. The removal of some of the gold atoms from the Au 25 core changes the core and a new cluster is formed.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Etching of gold nanoparticles by excess thiols is known. [12][13][14][15]20] During interfacial etching at 25 8C, octanethiol etches Au 25 at the water-toluene interface and the etched gold atoms along with some glutathione ligands form Au I SG thiolate, which precipitates. The removal of some of the gold atoms from the Au 25 core changes the core and a new cluster is formed.…”
Section: Resultsmentioning
confidence: 99%
“…Synthesis of Au 25 SG 18 : Au 25 SG 18 was synthesized from the as-prepared Au@SG clusters by ligand etching. [12][13][14][15] The as-prepared Au@SG cluster was dissolved in water (25 mL). GSH was added (614 mg) and stirred at 55 8C.…”
Section: Wwwchemeurjorgmentioning
confidence: 99%
See 2 more Smart Citations
“…Gold nanoparticles can be stabilized by anionic ligands such as carboxylic acid derivatives like citrate, tartrate, and lipoic acid (Peng et al 2007). Earlier studies showed that glutathione used for capping gold quantum clusters (AU-n-SG-m) (−SG, glutathione thiolate) is one such group of compounds which has been well known for the stability of the AUNPs synthesized chemically (Habeeb and Pradeep 2007). Moreover, he confirmed in his results that the bigger clusters, n  > 25, can be converted into AU25SG18 by adding excess GSH.…”
Section: Resultsmentioning
confidence: 99%